Living with a Stoma After Surgical Resection for Rectal Cancer: An Interpretive Phenomenological Study to Understand How Stomas Can Affect Physical Activity - Saunders, Stephanie (Université d'Ottawa / University of Ottawa, 2018)
The benefits of physical activity for cancer survivors are numerous and well-substantiated. However, it is unclear how to accommodate specific cancer treatments, such as a stoma as part of treatment for rectal cancer, in order to be physically active. To bridge this gap, this study undertook an interpretive phenomenological analysis to explore the experience of 15 rectal cancer survivors' engagement in physical activity with a stoma. Overall, three themes were found: 1) understanding the drive and the motivation to be physically active, 2) despite being motivated to be physically active with a stoma it can be challenging, and 3) how to be physically active with a stoma: lessons learned. The findings suggest rectal cancer survivors with a stoma require motivational support and enhanced competence and self-efficacy in order to engage in greater physical activity. Incorporating these skills into current information and supportive services targeting rectal cancer survivors with a stoma may help promote physical activity in this population.
Keywords: Cancer; Physical activity; Stoma; Ostomy